2021
DOI: 10.1002/aic.17444
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of frictional charging and electrostatic interaction of particles

Abstract: Triboelectrification due to frictional contacts between particles and surfaces is prevalent in many powder handling processes. Aiming to explore the friction-induced electrostatic charging behavior, a discrete element method (DEM) is developed for the first time in the current article, in which a frictional charging model and electrostatic interaction models are implemented. The charge accumulation on both the particles and the surface in a rotational container is then analyzed numerically and experimentally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…To determine the contact forces for elastic particles, Hertz theory is used to model the normal contact, while the theory of Mindlin and Deresiewicz is applied to calculate the tangential forces. 43,44 The translational and rotational movements of a particle are expressed by…”
Section: Volume Expansion and Softening During Swellingmentioning
confidence: 99%
See 2 more Smart Citations
“…To determine the contact forces for elastic particles, Hertz theory is used to model the normal contact, while the theory of Mindlin and Deresiewicz is applied to calculate the tangential forces. 43,44 The translational and rotational movements of a particle are expressed by…”
Section: Volume Expansion and Softening During Swellingmentioning
confidence: 99%
“…E * and r * are effective elastic modulus and the effective radius in contact; E a , E b , νa, νb, rp,a, and rp,b are the elastic moduli, Poisson's ratios and radii of the contacted objects, respectively. In addition, according to the overlap and the effective radius in contact, the radius of the contact area can be calculated as 43,44 ritaliccon=δnr*. …”
Section: Dem‐cfd Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Coupled DEM-CFD (Computational Fluid Dynamics) studies showed the detailed motion of particles from the initial dispersion in air through to the mouthpiece [ 21 , 22 , 23 , 24 , 25 ]. In the last decade, model formulations have been introduced to extend the particle-scale contact tracking capability of DEM with surface–surface charge transfer and physical electrostatic interaction models (see, e.g., [ 26 , 27 , 28 ]), allowing triboelectric charging phenomena at the particle scale to be studied [ 27 , 29 , 30 , 31 , 32 , 33 ]. Naik et al [ 34 ] studied the triboelectrification of binary mixtures of drug and excipient in a blender.…”
Section: Introductionmentioning
confidence: 99%
“…In the screw feeding process of food powder, the contact, collision, friction, and separation between powder particles and between the particles and the screw feeder cause a large amount of static electricity to accumulate in the powder (Hu et al, 2021). The powder carrying static electricity is easy to be adsorbed on the inner and outer walls of the packaging bag, causing poor quantitative accuracy of the packaging and incomplete heat sealing of the packaging bag; more serious is the accumulation of powder static electricity may cause the powder to catch fire, explosion, and other safety hazards (Bailey, 1984; Beloni & Dreizin, 2009, 2011; Boland & Geldart, 1972).…”
Section: Introductionmentioning
confidence: 99%